Exigência de metionina + cistina digestível para codornas japonesas nas fases de cria, recria e postura - Rodrigues, Taynara Prestes Perine Moretto (2018)
Four experiments were conducted to estimate nutritional requirements of digestible methionine + cystine for Japanese quails at growing and laying phases. To determine the requirements of the growth phase, experiment I was carried out on period of 1 to 14 days old (first phase), experiment II on period of 15 to 42 days old (second phase) and experiment III in the period of 43 to 168 days old (laying phase) with the objective of evaluating the residual effect of the treatments of the second phase. The experimental design (experiment I and II) was complete randomized (DIC) with 5 treatments (0.52, 0.64, 0.76, 0.88 and 1.00% methionine + digestible cysteine) and 5 replicates and in experiment III all birds received conventional diet. On experiment I were used 48 quails / experimental unit, on experiment II were used 31 quails / experimental unit, which were created until 14 days receiving conventional diet and in experiment III were selected 12 quails / experimental unit of experiment II to evaluate the residual effect. For the performance evaluation, parameters of feed intake (g / bird), body weight (g), weight gain (g), feed conversion (g / g) and viability (%) were analyzed. At 14 and 42 days old, the relative weight (%) of the liver, spleen, bursa, poultry warp were evaluated (%) and body chemical composition (%). The performance, productivity and egg quality parameters were evaluated during laying phase. In the first and second phases, quadratic effects (P<0.05) were observed for all performance variables and relative liver weight. On experiment I, a quadratic effect (P<0.05) was also observed for the relative weight of bursa. The laying performance results confirm the estimates obtained during the second phase, but there was no effect (P>0.05) on egg quality. Considering a better feed conversion, nutritional recommendation of digestible methionine + cysteine for Japanese quails at the first phase is 0.85% and at the second phase is 0.77%, both values higher than recommended by NRC (1994). At laying phase (experiment IV), an experiment was carried out with Japanese quails from 43 to 168 days old. Fifteen quails were used per experimental unit, totaling 375 birds. A total of 5 treatments (0.60, 0.75, 0.90, 1.05 and 1.20% methionine + cysteine) were used in a completely randomized design with 5 replicates. The performance parameters evaluated were feed intake (g / bird), body weight (g), egg weight (g), laying rate (%), egg mass (g eggs.bird.day-1 ), feed conversion by mass and dozen eggs (g.g-1 of eggs, g.dz-1 of eggs), viability (%) and the body chemical composition (%). The egg quality parameters were: % of component (yolk, albumen and shell relative to egg weight), specific gravity (g ml-1), Haugh unit, yolk index, shell weight per surface area and thickness of the shell (mm). Quadratic effect was found on the performance parameters evaluated (P<0.05), except for age at first egg and viability with linear effect. Body composition at 168 days of age showed a linear effect (P<0.05) on crude fat (%), fat deposition rate (g d-1) and retained energy in the carcass (Kcal g-1). On egg quality, the only variable that presented response to the tested levels was the thickness of the shell in an increasing linear (P<0.05). Regarding egg quality, no significant effect was observed on the variables tested (P>0.05). The nutritional recommendation of digestible methionine + cysteine for Japanese quails at laying phase is 0.90% from the maximum point obtained for the egg mass variable